2012
DOI: 10.1016/j.fct.2012.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Genetic toxicology evaluation of essential oil of Alpinia zerumbet and its chemoprotective effects against H2O2-induced DNA damage in cultured human leukocytes

Abstract: Essential oil (EO) of Alpinia zerumbet leaves, at non-toxic concentrations (50-300 μg/mL), did not induce genotoxicity in human leukocytes. However, at the highest concentration (500 μg/mL) tested caused a reduction in cell proliferation and viability, and an increase in DNA damage. Moreover, in vivo experiments showed that EO (400 mg/kg) did not exert mutagenicity on peripheral blood cells and bone marrow in mice. In DPPH test, EO showed scavenging effects against DPPH radicals, and other free radicals (deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 64 publications
(57 reference statements)
2
20
1
4
Order By: Relevance
“…Together, the results of the MTT and LDH release assays suggest that DDK and DK could exert a protective effect against H 2 O 2 -induced cytotoxicity. Our results corroborate those of a recent study, which reported that non-toxic concentrations of essential oil from A. zerumbet have a strong protective effect against H 2 O 2 -induced oxidative DNA damage in peripheral blood leukocytes (5).…”
Section: Discussionsupporting
confidence: 95%
“…Together, the results of the MTT and LDH release assays suggest that DDK and DK could exert a protective effect against H 2 O 2 -induced cytotoxicity. Our results corroborate those of a recent study, which reported that non-toxic concentrations of essential oil from A. zerumbet have a strong protective effect against H 2 O 2 -induced oxidative DNA damage in peripheral blood leukocytes (5).…”
Section: Discussionsupporting
confidence: 95%
“…Aliquot of oil was chromatographed in silica gel column and eluted with hexane, followed by chloroform and methanol. Crude oil and fractions were analyzed by gas chromatography coupled with mass spectrometry (GC-MS) and flame ionization detection (GC-FID) according to method described (Cavalcanti et al, 2012). GC-MS analysis was carried out on a Shimadzu QP5050 instrument equipped with non-polar OV-5 fused silica capillary column, while GC-FID analysis was carried out on a Shimadzu GC 2010 Plus instrument provided with non-polar CP-Sil-8 fused silica capillary column.…”
Section: Materials and Methods P L A N T M A T E R I A L E X T R A mentioning
confidence: 99%
“…Regarding the genotoxic potential of the essential oil from the Moro orange, no DNA damage in cells of the CCD‐1059Sk line was observed at the essential oil concentration used (Figure ; 200 μg/mL), so it can be safely used as a therapeutic agent. Cavalcanti et al evaluated the genotoxicity of the essential oil obtained from the leaves of Alpinia zerumbet using the Comet assay and found a chemical composition consisting of 98.3% monoterpenes. They observed that the essential oil did not induce genotoxicity in human leukocytes at concentrations of 50 to 300 μg/mL; however, at a concentration of 500 μg/mL, a decrease in cell viability and an increase in DNA damage were observed.…”
Section: Resultsmentioning
confidence: 99%